Porphyromonas gingivalis‐induced production of reactive oxygen species, tumor necrosis factor‐α, interleukin‐6, CXCL8 and CCL2 by neutrophils from localized aggressive periodontitis and healthy donors: modulating actions of red blood cells and resolvin E1. (5th May 2016) - Damgaard, C.; Kantarci, A.; Holmstrup, P.; Hasturk, H.; Nielsen, C. H.; Van Dyke, T. E.
Abstract : Background and Objectives: Porphyromonas gingivalis is regarded as a significant contributor in the pathogenesis of periodontitis and certain systemic diseases, including atherosclerosis. P. gingivalis occasionally translocates from periodontal pockets into the circulation, where it adheres to red blood cells (RBCs). This may protect the bacterium from contact with circulating phagocytes without affecting its viability. Material and Methods: In this in vitro study, we investigated whether human peripheral blood neutrophils from 10 subjects with localized aggressive periodontitis (LAgP) and 10 healthy controls release the proinflammatory cytokines interleukin (IL)‐6, tumor necrosis factor α (TNF‐α), the chemokine (C‐X‐C motif) ligand 8 (CXCL8; also known as IL‐8) and chemokine (C‐C motif) ligand 2 (CCL2; also known as monocyte chemotactic protein‐1) and intracellular reactive oxygen species (ROS) in response to challenge with P. gingivalis . In addition, the impact of RBC interaction with P. gingivalis was investigated. The actions of resolvin E1 (RvE1), a known regulator of P. gingivalis induced neutrophil responses, on the cytokine and ROS responses elicited by P. gingivalis in cultures of neutrophils were investigated. Results: Upon stimulation with P. gingivalis, neutrophils from subjects with LAgP and healthy controls released similar quantities of IL‐6, TNF‐α, CXCL8, CCL2 and intracellular ROS. The presence of RBCs amplified the release of IL‐6, TNF‐α and CCL2 statistically significant in both groups, but reduced the generation of ROS in the group of healthy controls, and showed a similar tendency in the group of subjects with LAgP. RvE1 had no impact on the production of intracellular ROS, TNF‐α, IL‐6, CXCL8 and CCL2 by neutrophils from either group, but tended to reduce the generation of ROS in subjects with LAgP in the absence of RBCs. Conclusions: Our data support that binding to RBCs protects P. gingivalis from ROS and concomitantly enhances neutrophil release of proinflammatory cytokines providing a selective advantage for P. gingivalis growth.